Efficacy and safety profiles of mechanical and pharmacological thromboprophylaxis - Ganau, Mario; Ligarotti, Gianfranco K. I.; Meloni, Marco; Chibbaro, Salvatore (Annals of Translational Medicine, 2019)
Venous thromboembolism (VT) has always attracted the attention of the scientific community as one of the most common causes of acquired morbidity and mortality in hospitalized patients. The objective of VT prophylaxis protocols is mostly aimed at preventing deep vein thrombosis (DVT) and pulmonary embolisms (PE). Their incidence may in fact be as high as 20% to 40% in high-risk populations, such as polytraumatized and critically ill patients (1). Although low-dose subcutaneous unfractionated heparin (UFH) or low molecular-weight heparin (LMWH) are estimated to reduce VT incidence by 50% (2), several studies (3-5) have demonstrated that mechanical prophylaxis with elastic compression and intermittent pneumatic compression (IPC) can further reduce the incidence of DVT/PE, and are widely advocated in at risk patients.